Determinants of Market Price of Share of Microfinance Institutions in Nepal - Narendra Sejuwal (Journal of Development and Administrative Studies, 2025)
This study examines the determinants of market price of share of Microfinance Institutions (MFIs) in Nepal, focusing on the impact of firm-specific and macroeconomic variables such as Price Earnings Ratio (P/E), Book Value Per Share (BVPS), Return on Assets (ROA), Gross Domestic Product (GDP), and Inflation (INF). Using secondary data from annual reports of 10 listed MFIs over a period of 10 years (2014/15 to 2023/24), the research employs descriptive statistics, correlation analysis, and multiple regression techniques to analyze the relationship between these factors and Market Price of Share (MPS). The results indicate that all selected variables have a statistically significant positive effect on the market price of shares. Specifically, the regression model explains approximately 48.5 percent of the variation in share prices, highlighting the importance of profitability, asset efficiency, and macroeconomic stability in influencing investor behavior and market valuation.